Spatial and temporal activity patterns of Amblyomma americanum - Daniel S. Marshall; Karen C. Poh; Mason V. Reichard; Lindsay A. Starkey; Jeb P. Owen (Parasites & Vectors)
Abstract Background Estimates of tick abundance and distribution are used to determine the risk of tick-host contact. Tick surveys provide estimates of distributions and relative abundance for species that remain stationary and wait for passing hosts (i.e. questing), but measures of tick populations may be less reliable for species that actively move in search of a host, such as Amblyomma americanum, the lone star tick (LST). Risk estimates for contact with adult LST require knowledge of the tick's spatial and temporal activity. Understanding the movement and the temporal patterns of host-seeking behavior will enhance risk assessment for LST. Methods Using CO2-baited traps over a 2-year period, we collected wild adult LST in Oklahoma. We used mark-recapture techniques to determine the distance ticks will travel, the proportion of the tick population that is detectable over time, and the relationship between tick abundance and the number of ticks detected in the field. Using video tracking software, we measured the distance traveled and activity time in the laboratory. Results In 24 h, LST travel up to 9 (mean = 3.2, SD = 3.6) m in the field and 36 (mean = 70.4, SD = 81.0) m in the laboratory. Marked LST were detectable in the environment for up to 14 days after release. We found that the number of recaptured ticks significantly increased with the relative abundance of ticks released, and at a minimum abundance (N = 1 tick released) LST were detectable 33.3% of the time. Across all experiments, fewer than half of marked ticks were recovered and at most 28.4% of ticks were detected with CO2-baited traps at any given time. Conclusions Our results show that LST actively move through the environment and pose a risk for host contact at distances of tens of meters. Ticks are detectable for several weeks, but only a fraction of them are detectable at any time. Larger numbers of ticks are detected as their population size increases, but even at very low numbers, LST are recovered with CO2 baiting. These spatial and temporal aspects of LST behavior should be considered when building predictive risk models of LST-host contact. Graphical Abstract